Mammalian Rap1 controls telomere function and gene expression through binding to telomeric and extratelomeric sites. - Martinez, P; Thanasoula, M; Carlos, A; Gómez-López, G; Tejera, A; Schoeftner, S; Dominguez, O; Pisano, D; Tarsounas, M; Blasco, M (2010)
Rap1 is a component of the shelterin complex at mammalian telomeres, but its in vivo role in telomere biology has remained largely unknown to date. Here we show that Rap1 deficiency is dispensable for telomere capping but leads to increased telomere recombination and fragility. We generated cells and mice deleted for Rap1; mice with Rap1 deletion in stratified epithelia were viable but had shorter telomeres and developed skin hyperpigmentation in adulthood. By performing chromatin immunoprecipitation coupled with ultrahigh-throughput sequencing, we found that Rap1 binds to both telomeres and to extratelomeric sites through the (TTAGGG)(2) consensus motif. Extratelomeric Rap1-binding sites were enriched at subtelomeric regions, in agreement with preferential deregulation of subtelomeric genes in Rap1-deficient cells. More than 70% of extratelomeric Rap1-binding sites were in the vicinity of genes, and 31% of the genes deregulated in Rap1-null cells contained Rap1-binding sites, suggesting a role for Rap1 in transcriptional control. These findings place a telomere protein at the interface between telomere function and transcriptional regulation.